Cicer arietinum as coagulant for water clarification / Meor Muhammad Hafiz Shah Buddin... [et al.] - Shah Buddin, Meor Muhammad Hafiz; Shuhaini, Muhammad Ibnu Hakim; Abd Halim,, Farah Adibah; Mohd Hafizal, Farris Aqil (Universiti Teknologi MARA Shah Alam, 2019)
This work aims to investigate the application of Cicer arietinum as an innovative coagulant for water clarification. Its coagulation ability for water clarification was demonstrated by treating lake water at average NTU of 146. Cicer arietinum was dried and ground to obtain uniform size of 500 µm. To achieve high turbidity removal from the polluted water, several parameters were studied including coagulant dosage, stirring speed and rapid mixing time. The turbidity removal, T(%), was determined using turbidity meter to track the suspended solids that have been coagulated with Cicer arietinum protein. Maximum turbidity removal (52.74%) was recorded by using 12 mg/L of coagulant at speed of 120 rpm for 4 mins. Additionally, the usage of Cicer arietinum as coagulant has hardly change the wastewater pH.